RESEARCH PAPER ON FINANCIAL DATA ANALYSIS AND TECHNICAL RESEARCH - Zawar , Uday; Shewale , Bhojraj; Sharma, Bhawana (International Journal of Research -GRANTHAALAYAH, 2025)
This research paper examines financial data analysis and technical research conducted during an internship at Opti Pro Trade Financial Services. It discusses how data-driven decision-making and analytical methods impact financial markets. The study combines theoretical knowledge with practical experience in market trends, investment decisions, and technical indicators. A case study on Reliance Industries Ltd. (RIL) demonstrates the use of technical tools like Moving Average Convergence Divergence (MACD), Relative Strength Index (RSI), and Simple Moving Averages (SMA) to pinpoint potential investment opportunities. The results show that using multiple indicators can greatly improve the accuracy of market predictions and decrease risk. The paper also looks at the challenges faced during financial research and ends with a discussion on the importance of ongoing learning in financial analytics.